Fuzzy rule base extraction by the improved bacterial memetic algorithm - Gál, László (2013)
In this paper we introduce new methods for handling knot order violation occurred in the Bacterial Memetic Algorithm (BMA) used for fuzzy rule base extraction. These methods perform slightly better than the method used before and are easier to integrate with the Bacterial Memetic Algorithm.